2001
DOI: 10.1254/jjp.87.177
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Drugs for the Treatment of Virus-Induced Chronic Hepatitis: From Hypercarcinogenic State to Hypocarcinogenic State

Abstract: ABSTRACT-Interferon (IFN)-based therapy is a standard treatment for chronic hepatitis caused by hepatitis C virus (HCV) infection. This treatment is effective in approximately 30 -40% of the patients and using ribavirin in combination with IFN increases the rate of sustained virologic clearance. For the remaining patients, glycyrrhizin is often used. Glycyrrhizin is known to prevent the development of hepatocellular carcinoma (HCC), but glycyrrhizin is usually administered intravenously. Drugs that are effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Angelica Dahuricae Radix contains various compounds including isoimperatorin, imperatorin, oxypeucedanin, byakangelicol, and byakangelicin. Of these agents, imperatorin, which is found in various plants used in traditional medicine, has recently been shown to have an inhibitory effect on mice concanavalin A-induced hepatitis (Okamoto et al, 1987). However, to the best of our knowledge, no studies conducted to date have reported the mechanism by which the anti-nociceptive and antiinflammatory action of methanol extract of Angelicae Dahuricae Radix (MEAD) occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Angelica Dahuricae Radix contains various compounds including isoimperatorin, imperatorin, oxypeucedanin, byakangelicol, and byakangelicin. Of these agents, imperatorin, which is found in various plants used in traditional medicine, has recently been shown to have an inhibitory effect on mice concanavalin A-induced hepatitis (Okamoto et al, 1987). However, to the best of our knowledge, no studies conducted to date have reported the mechanism by which the anti-nociceptive and antiinflammatory action of methanol extract of Angelicae Dahuricae Radix (MEAD) occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Counteracting the effects of Hepatitis C Virus (HCV) through the use of coumarins has proved challenging as only a small number, primarily osthole, are capable of inhibiting HCV replication and/or proliferation, this counteracting the progression of hepatitis C into hepatocarcinoma [136]. The action of osthole causes a strong reduction of plasma alanine aminotransferase and also inhibits caspase-3 activation [137].…”
Section: Structure Activity Relationships (Sars) Referencementioning
confidence: 99%
“…Osthole, a coumarin derivative contained in many medicinal plants especially in Boenninghausenia albiflora , was reported to protect against liver injury, and these effects are related to the presence of 7-methoxy and 3-methyl-2-butenyl groups in the structure [53,54]. Due to its low toxicity, osthole appears to be suitable for the treatment of chronic hepatitis and can be used as a lead compound for further development of orally ingested hepatoprotective drugs.…”
Section: Biological Activities Of Extracts and Ingredients Of Medicinmentioning
confidence: 99%